CACCI country profile Nepal - International Food Policy Research Institute (International Food Policy Research Institute, 2024)
Nepal is a mountainous, landlocked, and low-middle-income country in the South Asian region. Agriculture is the principal occupation housing 69% of the labor force, followed by tourism. Nepal witnesses frequent soil erosion, landslides, flash floods, and droughts with lasting impacts on most livelihoods. A recent Asian Development Bank study estimates that before 2050, the country will lose 2.2 percent of its yearly GDP to climate change. Energy, agriculture, water resources, forestry, biodiversity, and the health sector are at high risk due to the negative impact of climate change. The National Adaptation Plan (NAP) 2021 – 2050 is the guiding document along with the Second and the Third National Communication to the UNFCCC. The Second Nationally Determined Contribution (NDC) (Jan 2021 – Dec 2030) outlines the sectoral activity-based and policy targets and reduction in emissions in select sectors, all conditional on international support.